Problem Based Learning Model in Science Learning on Skills Developed in Elementary and Junior High Education Units - Nur Ainun; Maryati Maryati (Postgraduate, University of Mataram, 2024)
The purpose of this research is to see the competencies that can be formed through the use of problem-based learning (PBL) learning models. This research uses the Systematic Literature Review (SLR) method. This research analyzes search results from Google Scholar, publish or perish and semantic schoolar databases with a span of the last 10 years. Based on the search results, 150 relevant articles were obtained and then filtered based on the inclusion criteria, 46 articles were used as primary studies. Each article in the data, then analyzed based on the capabilities developed from the research results. The results of the analysis of this article review can be drawn conclusions and findings that the learning model (PBL) has a good impact on improving hardskill and softskill abilities in science learning both at the elementary and junior high school levels. At the elementary level, PBL is able to improve critical thinking skills and increase learning motivation, junior high school level can improve science literacy and learning independence